1996
DOI: 10.1177/106002809603000301
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Unbound Phenytoin Concentrations in the Critically Ill Neurosurgical Patient

Abstract: These results indicate that, in this population, the Sheiner-Tozer estimate of dphEF provides an unbiased, precise clinical estimate of dphF in patients for whom measured dphF is unavailable or impractical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…Despite this widespread use, there has been considerable controversy over whether inaccuracies in the model justify its use or not. Some authors have argued that since PHT free levels may not be readily available, the adjustment in cases of known hypoalbuminemia provides better guidance in dosing than the total PHT level obtained in the usual assay used for therapeutic drug monitoring [9,15,17]. In a population of "critically ill neurosurgical patients", Mlynarek et al concluded that the Sheiner-Tozer equation provided "an unbiased, precise clinical estimate" in cases where the PHT free level "is unavailable or impractical" [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this widespread use, there has been considerable controversy over whether inaccuracies in the model justify its use or not. Some authors have argued that since PHT free levels may not be readily available, the adjustment in cases of known hypoalbuminemia provides better guidance in dosing than the total PHT level obtained in the usual assay used for therapeutic drug monitoring [9,15,17]. In a population of "critically ill neurosurgical patients", Mlynarek et al concluded that the Sheiner-Tozer equation provided "an unbiased, precise clinical estimate" in cases where the PHT free level "is unavailable or impractical" [17].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have argued that since PHT free levels may not be readily available, the adjustment in cases of known hypoalbuminemia provides better guidance in dosing than the total PHT level obtained in the usual assay used for therapeutic drug monitoring [9,15,17]. In a population of "critically ill neurosurgical patients", Mlynarek et al concluded that the Sheiner-Tozer equation provided "an unbiased, precise clinical estimate" in cases where the PHT free level "is unavailable or impractical" [17]. For rural clinics in sub-Saharan Africa where malnutrition and AIDS are frequent, Fedler and Stewart concluded that the corrected value should be reported rather than the total phenytoin [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corrected total phenytoin ϭ total phenytoin ͑g/mL͒ ͕͓albumin ͑g/dL͒/4.4͔ ϫ 0.9͖ ϩ 0.1 [1] Based on the corrected concentration of total phenytoin, the estimated free phenytoin concentration can be obtained by multiplying by 0.1 (24). Statistical Analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The Sheiner-Tozer equation corrects the total phenytoin level for the corresponding serum albumin level, and has been found to be a useful tool to guide phenytoin dosing. [9][10][11] Phenytoin is primarily metabolised in the liver (>95%). Stowe et al, showed that children with severe, neurotrauma were found to have markedly altered protein binding and phenytoin metabolism, [12] and Markowsky et al, also demonstrated that phenytoin binding was significantly more variable with critical and convalescent patients with head injuries than healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%